A measurement of irradiance of light-curing units in dental offices in three Croatian cities - Ante Dundić; Valentina Rajić Brzović; Gloria Vlajnić; Danijela Kalibović Govorko; Ivana Medvedec Mikić (Medicinski Glasnik, 2021)
Aim To determine irradiance of light-curing units (LCUs) in dental offices in three Croatian cities and to compare irradiance values with the age and model of LCUs. Methods Private and public dental offices in three most prominent cities in Croatia (Rijeka, Split and Zagreb) were included in this study. In total, 195 LCUs were tested, using radiometer Ivoclar Bluephase Meter 2 for irradiance (mW/cm2 ). The minimum acceptable value was set at 400 mW/cm2 . The age, model and difference between declared and measured irradiance of the LCUs were also determined. Of the total of 195 LCUs, 190 (98%) were LED (light-emitting diode) and 5 (2%) were QTH (quartz-tungsten – halogen). Results The mean age of tested LCUs was 4.43±3.4 years; the oldest was in Rijeka, 5.2±3.8 years. The overall mean irradiance for all three cities was 806.4 mW/cm2 (p=0.0004). Of all LCUs, 11.3% were considered clinically unacceptable with irradiance of less than 400 mW/cm2 . Of all tested LCUs 42% (p=0.0005) had a 30% lower value of irradiance than the manufacturer of the LCU declared. In 73% tested LCUs, there was a matching between measured and declared irradiance. The age and model of LCUs had the most significant impact on irradiance. Conclusion The most commonly used LCU included in dental offices was LED. Mean irradiance was good enough to secure adequate polymerization of resin-based materials. Irradiance decreases with usage time of LCU.